Rapid Pathogen Identification With Direct Application of MALDI-TOF Mass Spectrometry on an Endophthalmitis Vitreous Sample Without Prior Culture. (July 2019) - Chun, Lindsay Y.; Dolle Molle, Laura; Schneewind, Olaf; Missiakas, Dominique; Beavis, Kathleen G.; Skondra, Dimitra
Purpose: We report a case of a 72-year-old man with bleb-related endophthalmitis (BRE) whose vitreous samples were directly analyzed with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) to rapidly identify the causative organism, whereas the results from conventional microbiological techniques were negative. Methods: We analyzed BRE vitreous samples with MALDI-TOF MS (Vitek MS, bioMérieux) for rapid pathogen identification without prior culture. Samples were also analyzed with standard microbiological methods. Results: Within 1 hour of sample acquisition, MALDI-TOF MS identified Gemella sanguinis from the undiluted vitreous sample from vitrectomy without prior culture with a confidence value of 99.7%. Gram stain and cultures from aqueous and vitreous samples were negative for 28 days after acquisition. The patient's right-eye vision improved from hand motion to 20/50 2 months later. Conclusions: Our findings suggest that the direct analysis of intraocular samples with MALDI-TOF MS could be a novel, promising adjuvant method of rapid endophthalmitis diagnosis.